The Spillover Effects of Adult Child's Schooling on Parent's Smoking Cessation: Evidence from China's Compulsory Schooling Reform - Liyang Xie; Xu Wei; Yi Zhou (Journal of Epidemiology and Community Health, 2021)
Objective: As elderly parents today will share a longer life with their children than ever before, the spillover effects of children's human capital on parents' wellbeing become increasingly important. This study investigated whether children's schooling leads parents to give up smoking and whether the effects were moderated by their education or child-parent contact frequency. Methods: Using data from the China Health and Retirement Longitudinal Study (CHARLS), we conducted an instrumental variable analysis using China's compulsory schooling reform in the 1980s as a natural experiment. Results: The Instrumental Variable (IV) estimates suggest that elderly parents of more highly educated children are more likely to quit smoking. Moreover, the effects are more significant among parents who had not finished primary school and also slightly stronger among parents who live close to their children or meet their children frequently. Discussion: Our findings add to current evidence on spillover effects of education in smoking cessation. A child's education may exert the impact through the spillover of health knowledge.